MAKNA PERIBAHASA BIMA PADA MASYARAKAT DESA WADUKOPA KECAMATAN SOROMANDI KABUPATEN BIMA - Nurwidayanti Nurwidayanti; Mahsun Mahsun; Ahmad Sirulhaq (Universitas Islam Negeri Mataram, 2025)
This research aims to describe the form and meaning of Bima proverbs in the Wadukopa Village community, Soromandi District, Bima Regency. The typa of research is descriptive qualitative research. The data source for this study is informants or the Wadukopa community. The data collection methode used in the study was through observation, interviews, and documentation. Observation data in the form of notes related to the behavior and interactions of informants, the interview data in the from information about proverb obtained through a question and answer process between the interviewer and the informant. While the documentation data in the form of written materials that have passed related to Bima proverbs. The data analysis method uses intralingual and extralingual equivalents. Intralingual iquivalents are used analyze the linguistic meaning in proverbs, while extralingual is used to understand how the culture context influence proverbs. Based on the result of the data analysis, it was found that the form of Bima proverbs in the Wadukopa community consists of proverbs in the form of proverbs, parable proverbs, and proverbs of proverbs/sayings. Meanwhile, the meaning of proverbs found in the Wadukopa village community is the denotative and connotative meanings as well as the cultures views of the community which are used to advise, motivative, provide support, remind and make the community aware, especially the younger generation who still lack knowledge. Proverbs can also be used to shape the character of the younger generation. By using proverbs in speaking, it is considered to prioritize politeness in language without saying it directly.